A long Early Pleistocene pollen record from Baza Basin (SE Spain): Major contributions to the palaeoclimate and palaeovegetation of Southern Europe. (1st March 2020) - Altolaguirre, Yul; Bruch, Angela A.; Gibert, Luis
Abstract: The basin of Baza is located in the central area of the Betic Range (SE Spain) with a catchment area of over 4000 km 2 . It contains a continuous and well preserved lacustrine sedimentary record from the Late Miocene to the Middle Pleistocene. The basin encloses numerous Miocene to Pleistocene mammal fossil sites that include some of the oldest hominin occurrences in Western Europe, found at the Orce sites. The present work features the palynological analysis of sediment samples obtained from the Palominas drill core. The Palominas core cuts thorough fine grained sedimentary units located in the depocenter of the basin, which contain well preserved pollen grains. The palynoflora found in the core is rich in herbaceous pollen, as well as Quercus and Pinus, with other tree taxa appearing in lesser quantities. Spectral analysis reveals strong climatically controlled vegetation successions. The application of the Biomization method on these assemblages allows for a reconstruction of the biome succession. The Early Pleistocene landscape was dominated by a sequence of steppe, evergreen-bushland and mixed-forest biomes. The Coexistence Approach method shows that SE Spain experienced humid periods, during which precipitations were significantly higher than during the modern climate. These humid phases are correlated with warm interglacial periods which featured the development of open forests. Dryer phases and fully open environments are correlated with colder glacial periods. Based on the palynoflora a Calabrian age is suggested for the Palominas core. The flora and climatic patterns identified in Baza are similar to the ones identified in Calabrian records of Southern Italy and Greece. Graphical abstract: Image 1 Highlights: The longest Early Pleistocene pollen record from continental deposits in Spain. The core could belong to the Calabrian stage, comprising over 400 kyr. Eleven humid phases are defined, superimposed by long-term climatic trends. A Mediterranean latitudinal gradient reflects drier and more open conditions in southern parts of Spain, Italy and Greece.